Decellularized xenogenic cartilage extracellular matrix (ECM) scaffolds for the reconstruction of osteochondral defects in rabbits. Issue 24 (7th June 2021) - Das, Piyali; Mishra, Rutusmita; Devi, Bavya; Rajesh, Kanike; Basak, Piyali; Roy, Mangal; Roy, Partha; Lahiri, Debrupa; Nandi, Samit Kumar
Abstract : The use of decellularized native allogenic or xenogenic cartilaginous extracellular matrix (ECM) biomaterials is widely expanding in the fields of tissue engineering and regenerative medicine. Abstract : The use of decellularized native allogenic or xenogenic cartilaginous extracellular matrix (ECM) biomaterials is widely expanding in the fields of tissue engineering and regenerative medicine. In this study, we aimed to develop an acellular, affordable, biodegradable, easily available goat conchal cartilaginous ECM derived scaffolding biomaterial for repair and regeneration of osteochondral defects in rabbits. Cartilages harvested from freshly collected goat ears were decellularized using chemical agents, namely, hypotonic–hypertonic (HH) buffer and Triton X-100 solution, separately. The morphologies and ultrastructure orientations of the decellularized cartilages remained unaltered in spite of complete cellular loss. Furthermore, when the acellular cartilaginous ECMs were cultured with murine mesenchymal stem cells (MSCs) (C3H10T1/2 cells), cellular infiltration and proliferation were thoroughly monitored using SEM, DAPI and FDA stained images, whereas the MTT assay proved the biocompatibility of the matrices. The increasing amounts of secreted ECM proteins (collagen and sGAG) indicated successful chondrogenic differentiation of the MSCs in the presence of the treated cartilage samples. In vivo biocompatibility studies showed no significant immune response or tissue rejection in the treated samples but tissue necrosis in control samples after 3 months. Upon implantation of the constructs in rabbits' osteochondral defects for 3 months, the histological and micro-CT evaluation revealed significant enhancement and regeneration of neocartilage and subchondral bony tissues. The IGF-1 loaded cartilaginous constructs showed comparatively better healing response after 3 months. Our results showed that decellularized xenogenic cartilaginous biomaterials preserved the bioactivity and integrity of the matrices that also favored in vitro stem cell proliferation and chondrogenic differentiation and enabled osteochondral regeneration, thus paving a new way for articular cartilage reconstruction.